Gene-Trait Matching and Prevalence of Nisin Tolerance Systems in Lactococus lactis - van Gijtenbeek, Lieke A.; Eckhardt, Thomas H.; Herrera-Domínguez, Lucía; Brockmann, Elke; Jensen, Kristian; Geppel, Asger; Nielsen, Kristian Fog; Vindeloev, Jannik; Neves, Ana Rute; Oregaard, Gunnar (Frontiers in Bioengineering and Biotechnology, 2021)
Lactococcus lactis cheese starter cultures typically contain a mix of many strains and may include variants that produce and/or tolerate the antimicrobial bacteriocin nisin. Nisin is well established as an effective agent against several undesirable Gram-positive bacteria in cheese and various other foods. In the current study, we have examined the effect of nisin on 710 individual L. lactis strains during milk fermentations. Changes in milk acidification profiles with and without nisin exposure, ranging from unaltered acidification to loss of acidification, could be largely explained by the type(s) and variants of nisin immunity and nisin degradation genes present, but surprisingly, also by genotypic lineage (L. lactis ssp. cremoris vs. ssp. lactis). Importantly, we identify that nisin degradation by NSR is frequent among L. lactis ssp.lactis and therefore likely the main mechanism by which dairy-associated L. lactis strains tolerate nisin. Insights from this study on the strain-specific effect of nisin tolerance and degradation during milk acidification is expected to aid in the design of nisin-compatible cheese starter cultures.